Editorial Underwater Acoustic Communications: Where We Stand and What Is Next? - Song, Aijun; Stojanovic, Milica; Chitre, Mandar (IEEE journal of oceanic engineering, 2019)
Underwater acoustic communications and networking technologies are critical tools for underwater exploration, subsea resource extraction, national defensemissions, etc. Their roles are becoming ever more important as nations around the globe turn to the oceans as sustainable sources of food and energy. The quest for acoustic communications has steadily intensified over the past two decades, addressing key issues of bandwidth efficiency, reliability, and latency, and focusing on adapting to the changing propagation conditions. These features are often at odds, as the nature of acoustic propagation forces tradeoffs on the system designer. For a high data rate, one must trade reliability; for full reliability, one must trade latency. While it is tempting to say that these channel-imposed constraints and tradeoffs are annoying, it is also true thatworkingwith the acoustic channel provides unique technical challenges and solutions that are not seen in other areas.